1992
DOI: 10.1246/cl.1992.1237
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Intramolecular Cycloaddition of o-Quinonemethides in Protic Solvent. An Efficient Synthesis of (−)-trans-Hexahydrocannabinol

Abstract: A very facile and efficient synthesis of (−)-trans-hexahydrocannabinol was achieved through the intramolecular Diels-Alder reaction of an o-quinonemethide derived from 2-(1-hydroxycitronellyl)olivetol 1,3-bismethoxymethyl ether in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…o- Quinonemethides 1 are very reactive intermediates in organic synthesis, and some natural products have been synthesized using [4 + 2] cycloaddition of these species as the key step (eq 1) . We have been investigating the generation and reaction of o- quinonemethides under mild conditions in order to widen the application of o- quinonemethides in organic synthesis . Previously, we reported that treatment of the phenol derivative 2 with a catalytic amount of an acid in methanol at reflux gave the tricyclic compound 3 in high yield as the sole stereoisomer (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…o- Quinonemethides 1 are very reactive intermediates in organic synthesis, and some natural products have been synthesized using [4 + 2] cycloaddition of these species as the key step (eq 1) . We have been investigating the generation and reaction of o- quinonemethides under mild conditions in order to widen the application of o- quinonemethides in organic synthesis . Previously, we reported that treatment of the phenol derivative 2 with a catalytic amount of an acid in methanol at reflux gave the tricyclic compound 3 in high yield as the sole stereoisomer (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…o- Quinonemethides 4 were thought to be generated by elimination of methanol from 6 , which in turn, could be formed by acetal-exchange reaction between salicylaldehyde dimethyl acetal ( 7 ) and the unsaturated alcohol 8 . It is also of great interest to see whether o- quinonemethides 4 have enough reactivity toward electron-rich dienophiles or show rather weak reactivity like 6- p -methoxybenzylidene-3,4-methylenedioxy-2,4-cyclohexadien-1-one ( 9 ), 1f,3d which is known as a stable and isolable o- quinonemethide.
…”
Section: Introductionmentioning
confidence: 99%
“…10 Unreacted 12 was recycled. Exposure of 14 to toluene-sulfonic acid (TsOH) in MeOH at reflux 11 gave a modest yield of dihydrobenzopyran 15 accompanied by larger amounts of tetrahydrofuran 16. † The tetrahydrofuran probably results from a stepwise, ionic process.…”
Section: Omementioning
confidence: 99%
“…The observed stereochemistry could not have been predicted with confidence from the outset. Cyclization to form the C9 methyl cannabinoid skeleton is known from precedent 11 to produce the C6a-C10a trans stereoisomer. Our own work 13 has shown that cyclization to form the D 9 unsaturated series produces the unnatural C6a-C10a cis stereoisomer as the exclusive product, therefore the stereochemical outcome of the cyclization is easily perturbed by minor structural changes in the seco precursor (cf.…”
Section: Omementioning
confidence: 99%
“…This self-induced non-equivalence appears to be caused by diastereoisomeric solute-solute interactions, and it is therefore possible to use NMR to determine the ee of a sample of (614) without employing a chiral shift reagent.553 Most of the (chemical) activity in this area has focused on synthesis. Citronella1 (53) reacts with phenols in refluxing quinoline to yield hexahydrocannabinoids (6 15) via intermediate quinone methides (61 6).554 Activated phenols can be A similar route has been employed in a synthesis of ( -)-trans-hexahydrocannabinol (61 7), 556 The derivative (61 8) undergoes a related intramolecular reaction to yield 9-nor-9hydroxyhexahydrocannabinol (6 1 9). j5' Apoverbenone (620) has been converted into the racemic 11nor-9-carboxy -Ag-tetrahydrocanna bin01 carboxylic acid (62 1) which is the principle human metabolite of Ag-tetrahydrocannabinol (622).…”
Section: Lridanesmentioning
confidence: 99%